Rational inefficiency and non-performing loans in Chinese banking: A non-parametric bootstrapping approach - Kent Matthews; Jianguang Guo; Nina Zhang (Cardiff University, Cardiff Business School, 2007)
The existing Chinese banking system was born out of a state-planning framework focussed on the funding of state-owned enterprises. Despite the development of a modern banking system, numerous studies of Chinese banking point to its high level of average inefficiency. Much of this inefficiency relates to the high level of non-performing loans held on the banks books. This study argues that a significant component of inefficiency relates to a defunct bureaucratic incentive structure. Using bootstrap non-parametric techniques the paper decomposes cost-inefficiency into X-inefficiency and rational inefficiency caused by bureaucratic rent seeking. In contrast to other studies of the Chinese banking sector, the paper argues that a change in the incentive structure and the competitive threat of the opening up of the banking market in 2007 has produced reduced inefficiency and improved performance.
Keywords: D23; G21; G28; 330; Bank Efficiency; China; X-inefficiency; DEA. Bootstrapping; Bank; Kreditrisiko; Notleidende Kredite; X-Effizienz; Data-Envelopment-Analyse; China